Numerical simulation of the high-latitude non-stationary ionospheric Alfvén resonator during an IPDP event - Prikner, K; Mursula, K; Kangas, J; Feygin, F.Z; Kerttula, R
The ionospheric Alfvén resonator (IAR) was numerically simulated under non-stationary ionospheric and magnetospheric conditions of the IPDP event of December 4, 1986. The full numerical wave method was applied using height profiles of the ionospheric plasma parameters obtained from the Scandinavian EISCAT radar measurements close to the Ivalo latitude. An attempt to model the inverse problem of numerical simulation - prolongation of the electron density profiles at altitudes above the ionospheric F layer - was made on the basis of the IAR simulation in correlation with the IPDP frequency increase. The change of the IAR wave characteristics during the substorm was illustrated by height profiles of the total wave amplitude and various polarization characteristics, taking into consideration the ordinary L-mode and the extraordinary R-mode waves for parallel and non-parallel incidence with respect to the magnetic field line. K. Prikner, K. Mursula, J. Kangas, F.Z. Feygin, R. Kerttula. Obsahuje bibliografii